Optimal sensitometric curves of Kodak EDR2 film for dynamic intensity modulated radiation therapy verification - Suriyapee, S (Department of Biomedical Imaging, Faculty of Medicine, University of Malaya, Malaysia, 2008)
PURPOSE: To investigate the optimal sensitometric curves of extended dose range (EDR2) radiographic film in terms of depth, field size, dose range and processing conditions for dynamic intensity modulated radiation therapy (IMRT) dosimetry verification with 6 MV X-ray beams. MATERIALS AND METHODS: A Varian Clinac 23 EX linear accelerator with 6 MV X-ray beam was used to study the response of Kodak EDR2 film. Measurements were performed at depths of 5, 10 and 15 cm in MedTec virtual water phantom and with field sizes of 2x2, 3x3, 10x10 and 15x15 cm(2). Doses ranging from 20 to 450 cGy were used. The film was developed with the Kodak RP X-OMAT Model M6B automatic film processor. Film response was measured with the Vidar model VXR-16 scanner. Sensitometric curves were applied to the dose profiles measured with film at 5 cm in the virtual water phantom with field sizes of 2x2 and 10x10 cm(2) and compared with ion chamber data. Scanditronix/Wellhofer OmniPro(TM) IMRT software was used for the evaluation of the IMRT plan calculated by Eclipse treatment planning. RESULTS: Investigation of the reproducibility and accuracy of the film responses, which depend mainly on the film processor, was carried out by irradiating one film nine times with doses of 20 to 450 cGy. A maximum standard deviation of 4.9% was found which decreased to 1.9% for doses between 20 and 200 cGy. The sensitometric curves for various field sizes at fixed depth showed a maximum difference of 4.2% between 2x2 and 15x15 cm(2) at 5 cm depth with a dose of 450 cGy. The shallow depth tended to show a greater effect of field size responses than the deeper depths. The sensitometric curves for various depths at fixed field size showed slightly different film responses; the difference due to depth was within 1.8% for all field sizes studied. Both field size and depth effect were reduced when the doses were lower than 450 cGy. The difference was within 2.5% in the dose range from 20 to 300 cGy for all field sizes and depths studied. Dose profiles measured with EDR2 film were consistent with those measured with an ion chamber. The optimal sensitometric curve was acquired by irradiating film at a depth of 5 cm with doses ranging from 20 to 450 cGy with a 3×3 cm(2) multileaf collimator. The optimal sensitometric curve allowed accurate determination of the absolute dose distribution. In almost 200 cases of dynamic IMRT plan verification with EDR2 film, the difference between measured and calculated dose was generally less than 3% and with 3 mm distance to agreement when using gamma value verification. CONCLUSION: EDR2 film can be used for accurate verification of composite isodose distributions of dynamic IMRT when the optimal sensitometric curve has been established.